2022
DOI: 10.1111/trf.17028
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for intravenous immunoglobulin‐related hemolysis: A systematic review of clinical trial and real‐world populations

Abstract: Background: Severe hemolysis rarely occurs in patients receiving intravenous immunoglobulin (IVIG) therapy. A systematic review was performed to assess the incidence of IVIG-related hemolysis and the impact of patient and product risk factors. Study Design and Methods: A systematic literature search for terms related to "IVIG products", "hemolysis," and "adverse events" was conducted in Embase for articles published between January 1, 2015, and May 31, 2021. Studies with no clinical datasets, no IVIG treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…Risk factors identified in this study (non-O blood group recipients and dose) have been previously reported in numerous prospective and retrospective studies [2]. Patients of blood groups A, B and AB were at greater risk of haemolysis compared with group O patients likely because of the passive transfer of ABO antibodies in the IVIG product.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Risk factors identified in this study (non-O blood group recipients and dose) have been previously reported in numerous prospective and retrospective studies [2]. Patients of blood groups A, B and AB were at greater risk of haemolysis compared with group O patients likely because of the passive transfer of ABO antibodies in the IVIG product.…”
Section: Discussionsupporting
confidence: 55%
“…The most frequent types of reactions to IVIG included: FNHTR (30.8%), minor allergic 1 Sites that are required to report moderate to severe reactions only. 2 Sites that report all reactions (mild, moderate and severe); the analysis of reaction frequency and rate included only reactions reported between 2014 and 2021 (n = 568/620 reactions). (antipyretics, antihistamines, corticosteroids, diuretics, sedatives and epinephrine) were not administered before transfusion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations